Principles of Microeconomics - Kolmar, Martin (Springer, 2017)
One may wonder why I think that it makes sense to add yet another introductory textbook to the overfilled shelf of well-established books on microeconomics. There are three reasons that motivated me to do so. First, a lot of textbooks in economics want to make one believe that the theories presented are more or less context-free and objective. This is a wrong and dangerous belief. First of all, all theories are embedded in an intellectual milieu from which they borrow and on which they build. No man is an island, and no scientific theory is either. The tendency to shun any contextualisations of the theories comes at the risk of blindness towards the implicit assumptions, value judgements and epistemes on which the theory depends. This makes economics prone to being misused for ideological purposes. Economic literacy does not only mean that one is able to understand the rules and patterns of modern economies, but also that one understands how economic theories relate to other social sciences and the culture from which they emerge. This textbook is an attempt to contextualize modern economics in the hope that students will get a better overview of its strengths and weaknesses. It puts also a specific emphasis on case studies that range widely from the functioning of coffee markets, the logic of overfishing, to price discrimination in the digital age. This approach makes this book also potentially interesting for students who study economics as a minor and who want to understand how economic theories relate to other social sciences and how they can be used to better understand markets as well as phenomena like climate change, among many others. To make it easier to identify the most important contextualizations in this book, I work with a series of icons that one will find in the margins of this book. L indicates a legal, B a business, and ˆ a philosophical (broadly speaking) context. Furthermore, one will find the most important definitions and technical terms highlighted with a✍-sign in the margins of the book.
An Integrative Approach